Water Content And Weight Loss Changes Of White Oysters Mushroom (Pleurotus Ostreatus) During Storage - Doli Siregar, Ias Marroha; Pratama, Filli; Hamzah, Basuni; Wulandari, Wulandari (Universitas Djuanda, 2023)
White oyster mushroom is one type of mushroom that is popular in Indonesia. This study aims to determine the rate of change in water content and weight loss of white oyster mushrooms during storage. This study used a Completely Randomized Factorial Design with two treatments with 3 replications. The first treatment (A) was the difference in storage temperature (10, 20 and 30oC) and the second factor (B) was the difference in CO2 gas concentration (control, 20, 30 and 40%). Parameters observed were water content and weight loss. The results showed that the water content before storage was 90.47%, after storage at a temperature of 10oC for 10 days increased in the range 92.71% - 93.81%. The temperature 20oC for 8 days increased in the range 93.54% - 94.02%, while at 30oC for 3 days it increased 94.36%. White oyster mushroom weight before storage ranged from 100.00 g - 110.00 g after storage at 10oC for 10 days weight loss in the range of 2.04% - 2.1%. Storage temperature of 20oC for 8 days decreased in the range of 2.37% - 2.90%, while at 30oC for 3 days it experienced 4.01%. The Q10 value of the highest water content change was obtained at the addition of 30% CO2 with a value of 3.00. The Q10 value of the highest weight loss change was obtained at the addition of 0% CO2 with a value of 1.18.